Miniaturized Low-Cost High-Performance Digital Radar - Taghadosi, Mansour (2015)
A Master of Science thesis in Electrical Engineering by Mansour Taghadosi entitled, "Miniaturized Low-Cost High-Performance Digital Radar," submitted in May 2015. Thesis advisors are Dr. Lutfi Albasha and Dr. Hasan Mir. Soft and hard copy available.